Pelatihan Interactive English Speaking Games untuk Meningkatkan Kepercayaan Diri Berbahasa Inggris Peserta Didik Anak Jalanan Kelas X di Yayasan Insan Mandiri Kota Depok - Ratna Wulandari; Aswarini Sentana; Anindia Ayu Rahmawati; Adani Nur Sabrina; Septian Dwi Putri; Ricky Perdana; Stella Amanda; Marliana Marliana (TRIDHARMADIMAS: Jurnal Pengabdian Kepada Masyarakat Jayakarta, 2026)
Lack of self-confidence is the primary psychological barrier for street children in mastering English speaking skills. This community empowerment research, employing a quasi-experimental design, aims to enhance the English-speaking confidence of grade X street children at the Insan Mandiri Foundation, Depok, through Interactive English Speaking Games. The program was conducted from March to June 2026, involving a saturated sample of 45 tenth-grade students. The research design utilized a One-Group Pretest-Posttest Design executed over 12 intensive sessions. The intervention was developed based on scaffolding principles using various interactive games, such as Word Chain, Situational Role-Play, and Two Truths and a Lie. Evaluation metrics were collected via a modified Foreign Language Classroom Anxiety Scale (FLCAS) self-confidence questionnaire and a speaking performance rubric. The pre-test results revealed that the majority of students fell into the "Low" category (57.8%). However, post-intervention (post-test), 62.2% of students successfully achieved the "High" category, and 26.7% reached the "Very High" category. The accumulative mean score of students' self-confidence sharply rose from 42.4 to 78.6, with a significant value of p = 0,000 (p < 0,05). It can be concluded that the implementation of interactive games over 12 sessions is highly effective in lowering the affective filter, mitigating language anxiety, and significantly boosting the self-confidence of street children.